Prostate cancer early detection: Clinical practice guidelines in oncology™ - Kawachi, M; Bahnson, R; Barry, M; Busby, J; Carroll, P; Carter, H; Catalona, W; Cookson, MS; Epstein, J; Etzioni, R; Giri, V; Hemstreet, G; et al. (2010)
Since the early 1990s, many variants of the tPSA assay have been introduced to increase the sensitivity of screening programs (cancer detection) while maintaining specificity (elimination of unnecessary biopsies). Again, these guidelines recommend ways that individuals and their physicians can use these new techniques rationally for early detection of prostate cancer. These guidelines are not designed to provide an argument for using population screening programs for prostate cancer, but are meant to provide a vehicle for practicing early detection efforts in an evidence-based, systematic fashion in patients who choose to participate in these programs. Whether to treat a patient on diagnosis is beyond the scope of these guidelines (see NCCN Clinical Practice Guidelines in Oncology: Prostate Cancer [in this issue; to view the most recent version of these guidelines, visit the NCCN Web site at www.NCCN.org]). These guidelines incorporate many new validated findings in addition to the DRE and tPSA test, including percent fPSA, PSAV, cPSA, biopsy pathology, and TRUS-guided biopsy techniques. The panel will re-examine the clinical efficacy of these new modalities annually, and the guidelines will be modified accordingly. In addition, future iterations of these guidelines may incorporate new serum markers currently undergoing clinical investigation. The goal of the NCCN and this guideline panel in updating these algorithms is to help men and clinicians choose a program for early detection of prostate cancer and make decisions about the need for prostate biopsy. Any clinician who uses these guidelines is expected to exercise independent medical judgment in the context of the individual clinical circumstances to determine each patient's need for prostate biopsy. These guidelines will continue to evolve as the field of prostate cancer advances. © Journal of the National Comprehensive Cancer Network.